2008
DOI: 10.1371/journal.pone.0002684
|View full text |Cite
|
Sign up to set email alerts
|

Implication of New WHO Growth Standards on Identification of Risk Factors and Estimated Prevalence of Malnutrition in Rural Malawian Infants

Abstract: BackgroundThe World Health Organization (WHO) released new Child Growth Standards in 2006 to replace the current National Center for Health Statistics (NCHS) growth reference. We assessed how switching from the NCHS to the newly released WHO Growth Standards affects the estimated prevalence of wasting, underweight and stunting, and the pattern of risk factors identified.Methodology/Principal FindingsData were drawn from a village-informant driven Demographic Surveillance System in Northern Malawi. Children (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
3

Year Published

2009
2009
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 15 publications
7
30
3
Order By: Relevance
“…Through this process concerns were raised (13)(14)(15)(16) and strengths were noted (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) . The detailed evaluation made it possible to quantify the impact of the new standards on estimates of prevalence of malnutrition (28)(29)(30)(31)(32)(33)(34) and their implications for child health programmes .…”
Section: Discussionmentioning
confidence: 99%
“…Through this process concerns were raised (13)(14)(15)(16) and strengths were noted (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) . The detailed evaluation made it possible to quantify the impact of the new standards on estimates of prevalence of malnutrition (28)(29)(30)(31)(32)(33)(34) and their implications for child health programmes .…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent studies have investigated the direction and magnitude of these differences. [9][10][11][12] In children aged months, the prevalence of stunting (i.e. low height-for-age) and wasting (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…low weight-for-age) was lower. 9,11,12 In the first half of infancy (i.e. the period from birth up to the end of the 6th month), the prevalence of stunting, wasting and underweight has been reported to be higher with WHO growth standards.…”
Section: Introductionmentioning
confidence: 99%
“…When using the WHO standards compared with the NCHS reference, other studies also found a higher proportion of stunted children (9,10,12) and a lower proportion of underweight children (8)(9)(10)12) . However, the proportion of wasted children, indicated by a WHZ of #22?00, showed more variable results.…”
Section: Discussionmentioning
confidence: 94%